Breast‐cancer‐isation explored: Social experiences of gynaecological cancer in a Norwegian context. Issue 8 (27th July 2016) - Solbrække, Kari Nyheim; Lorem, Geir
Abstract: This article's point of departure is recent claims that breast cancer survivorship displaying positivity and self‐growth represents the gold standard for all forms of cancer survivorship in English‐speaking Western cultures. An interview study of Norwegian women regarding gynaecological cancer followed by hysterectomy is used to explore whether this process is taking place beyond this setting. Results show that the women's experiences of having to display survivorship in this manner are not as notable as found in English‐speaking Western countries, neither is their experience of social othering. Reasons for this may be strong norms of social egalitarianism marking Norwegian culture and breast cancer informational campaigns that have not yet totally defined Norwegian norms for how to survive cancer. At the clinic and in the public sphere, however, the women experience gynaecological cancer as clearly having lower status than breast cancer, leading to a strong sense that the bodily site of their disease is taboo. Hence, as found in English‐speaking cultures, the complex embodied nature of having gynaecological cancer and life beyond treatment seems to be silenced by the media and medical institutions. Finally, implications for future research and health care related to cancer survivorship are also discussed.